(untitled) (Iranian Journal of Kidney Diseases, 2021)
Sarcoidosis is a multisystemic granulomatous disease of unknown etiology. Renal involvement in sarcoidosis patients is occurred, but the incidence and prevalence is uncertain. The most common renal involvement of systemic sarcoidosis is nephrocalcinosis and interstitial nephritis. After sarcoidosis was diagnosed in a 31-year-old male patient, we performed a renal biopsy because of nephrotic range proteinuria and renal dysfunction. The collapsing variant of focal segmental glomerulosclerosis (FSGS) secondary to sarcoidosis was diagnosed by kidney biopsy.